2019
DOI: 10.3390/cells8121634
|View full text |Cite
|
Sign up to set email alerts
|

The Butterfly Effect of RNA Alterations on Transcriptomic Equilibrium

Abstract: Post-transcriptional regulation plays a key role in modulating gene expression, and the perturbation of transcriptomic equilibrium has been shown to drive the development of multiple diseases including cancer. Recent studies have revealed the existence of multiple post-transcriptional processes that coordinatively regulate the expression and function of each RNA transcript. In this review, we summarize the latest research describing various mechanisms by which small alterations in RNA processing or function ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 196 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…Others have similarly shown that cells display a sensitive dependence to initial conditions (in this case, gene expression), and that very small changes in transcriptional regulation and equilibrium may exert potent perhaps even chaotic impacts on disease progression (90,91).…”
Section: Discussionmentioning
confidence: 99%
“…Others have similarly shown that cells display a sensitive dependence to initial conditions (in this case, gene expression), and that very small changes in transcriptional regulation and equilibrium may exert potent perhaps even chaotic impacts on disease progression (90,91).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we may under- or overestimate biological effects based on our interpretation of the differential gene expression results 24 h after injection. Also, posttranscriptional ( 87 ) and posttranslational mechanisms ( 88 ) may account, among other things, for a non-linear correlation between mRNA and protein abundance. These shortcomings may also contribute to an explanation as to why the CLH, which features many of the same differentially regulated gene transcripts as the ILH, does not feature morphological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…What is being detected in this study are the further downstream (larger) effects of a biological pathway initiated at the base change. Reminiscent of a "butterfly effect", where a single base change can lead to a cascade of changes, leading to increasingly larger effect sizes down the biological pathway that can be more readily detected [16,17]. Receiver Operating Characteristic (ROC) curves for PRS were generated for the BDR cohort using the IGAP (A) and Jansen (B) summary statistics.…”
Section: Discussionmentioning
confidence: 99%